Designing an Android-based Audio Calculator with Mit App Inventor for Visually Impaired Students - Putri, Meirizka Hani; Sarnita, Fitria; Ahyar, Ahyar (JUSTIN (Jurnal Sistem dan Teknologi Informasi), 2024)
The selection of learning media must be in accordance with the circumstances and needs of students. Blind students are special students who do not differ much in cognitive abilities with students in general, therefore the purpose of this study is to create learning media that can be used by blind students to learn basic arithmetic operations. The application development method uses the Agile method and the development model uses scrum so that application development can run optimally and the application can reach the desired stage. SLB Baiturrahman Sondosia's visually impaired students still use the counting method using fingers on addition and subtraction operations, for multiplication, division and powers and numbers they still have difficulty especially in the powers and numbers operation whose concept they do not understand. However, they can already apply basic arithmetic operations in everyday life such as adding up their money and then subtracting, dividing and multiplying it. This shows that blind students have basic numeracy skills. The audio calculator application has passed the media expert validation test and is declared suitable for use. The Audio Calculator application has been applied to blind students at SLB Baiturrahman Sondosia as learning media used by teachers. When students use the application, it seems that students get a new learning experience, they are enthusiastic and find it easier to memorize and deepen their counting skills both independently and with the help of teachers at school.